2015
DOI: 10.1177/1550059415590750
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative EEG Neurometric Analysis–Guided Neurofeedback Treatment in Dementia

Abstract: Dementia is a debilitating degenerative disorder where the sufferer's cognitive abilities decline over time, depending on the type of dementia. The more common types of dementia include Alzheimer's disease and vascular or multi-infarct dementia. In this study, 20 subjects with dementia (9 of Alzheimer's type, and 11 with vascular dementia) were treated using qEEG-guided neurofeedback training. The Mini Mental Status Examination (MMSE) was used as the primary outcome measure. The results showed an increase of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…Additional success has been reported using EEG-based NF for attention training and WM in young adults (Egner and Gruzelier, 2001; Zoefel et al, 2011; Ros et al, 2013, 2014), in post-traumatic stress disorder (Ros et al, 2016), and in older dementia patients (e.g., Surmeli et al, 2016). We summarize some of the recent studies on attention or WM training in older and younger adults in Table 1.…”
Section: Advancement In Brain Training Methodologymentioning
confidence: 96%
“…Additional success has been reported using EEG-based NF for attention training and WM in young adults (Egner and Gruzelier, 2001; Zoefel et al, 2011; Ros et al, 2013, 2014), in post-traumatic stress disorder (Ros et al, 2016), and in older dementia patients (e.g., Surmeli et al, 2016). We summarize some of the recent studies on attention or WM training in older and younger adults in Table 1.…”
Section: Advancement In Brain Training Methodologymentioning
confidence: 96%
“…[25][26][27] In addition, neurofeedback has been successfully introduced in clinical practice to reduce progression of cognitive dysfunction in patients diagnosed with cognitive problems and dementia. [28][29][30][31] The QEEG findings of increased frontal/temporal delta and theta powers in an early dementia patient correlates well with evidence of decreased metabolism in the same regions identified on PET imaging. However, as we know QEEG testing is less expensive and does not require the injection of a radioactive tracer.…”
Section: Discussionmentioning
confidence: 82%
“…25-27 In addition, neurofeedback has been successfully introduced in clinical practice to reduce progression of cognitive dysfunction in patients diagnosed with cognitive problems and dementia. 28-31…”
Section: Discussionmentioning
confidence: 99%
“…Wang and Hsieh (2013) found that theta band power training of healthy older participants was successful with regard to EEG findings as well as in improving attention and working memory. In a study where participants diagnosed with either AD or vascular dementia were trained using quantitative EEG-guided neurofeedback (Surmeli et al, 2016), regardless of the dementia In a recent pilot observational non-controlled study we showed an improvement in memory performance after delivering 10 sessions of neurofeedback (Lavy et al, 2019). This was accompanied by an incremental increase in the PAF.…”
Section: Introductionmentioning
confidence: 79%